Kinari Traditional Food Packaging Development - Syukri, Daimon; Azima, Fauzan; Sayuti, Kesuma; Yenrina, Rina; Novizar, Novizar; Anggraini, Tuty (Institute of Research And Community Service, Andalas University / LPPM Universitas Andalas, 2022)
This community service activity carried out by the Faculty of Agricultural Technology, University of Andalas Padang, is in collaboration with Nagari Kinari, Bukit Sundi District, Solok City. The activity location is at the Nagari Kinari office which has been prepared very well. Nagari Kinari has many Micro, Small and Medium Enterprises (MSMEs) such as salamak pangekbanana, rendang aina and kalio baluik. In this era, packaging is very important to maintain the shelf life of food and is a trend and a great opportunity for doing business. This opportunity only applies to products that have good packaging and good sterilization. However, this opportunity has not been taken by several MSMEs in Nagari Kinari, so that this application is expected to arouse the enthusiasm of MSMEs to immediately carry out good packaging for their business.